FAKTOR – FAKTOR YANG MEMPENGARUHI PENCAPAIAN TARGET CDR (Case Detection Rate) OLEH KOORDINATOR P2TB DALAM PENEMUAN KASUS DI PUSKESMAS KOTA SEMARANG - Yuniar Syahrin Vidyastari; Emmy Riyanti; Kusyogo Cahyo (Jurnal Kesehatan Masyarakat (Undip), 2019)
Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. Case finding of tuberculosis is one of the main strategies for tuberculosis control.One of the important roles in finding pulmonary TB cases is one of them is P2TB officers in each Puskesmas. This study aims to determine the factors that influence the achievement of the CDR Target (Case Detection Rate) in Case Findings in Semarang City Health Center.This research is a quantitative study with a cross sectional approach using total sampling techniques obtained by a sample of 37 P2TB officers in the Semarang City Health Center. Data collection is done through interviews with questionnaires. Data analysis was carried out by univariate and bivariate.The results of the study found that 20 officers (54.1%) had high CDR targets and 17 officers (45.9%) had low CDR targets. Most respondents were over 42 years old (78.3%) and the majority were female (81.08%). More than half of the respondents had nursing diploma for the last education (56.7%). The results showed that there were bound variables related to Knowledge (p = 0.015), Motivation (p = 0.037), Training (p = 0.014), Job Stress (p = 0.006).This study concluded that achieving CDR targets by P2TB officers in finding cases at the Semarang City Health Center was good. However, there were still officers who were less active in finding TB cases. therefore, the role of puskesmas and the government is needed in monitoring so that case discoveries run according to the specified targets.